Cerebrospinal fluid concentration of fibronectin in patients with HIV-1 infection and central nervous system disorders. Issue 11 (November 1993) - Torre, D; Zeroli, C; Ferrario, G; Bonetta, G; Fiori, G P; Martegani, R
Abstract : AIMS--To evaluate the fibronectin concentrations in the cerebrospinal fluid of HIV-1 infected patients with central nervous system disorders. METHODS--Fibronectin was determined by an immunoturbidimetric assay in 41 HIV-1 infected patients with AIDS dementia complex, progressive multifocal leucoencephalopathy, and opportunistic infections. RESULTS--A significant decrease in fibronectin concentrations in the cerebrospinal fluid of patients with AIDS and dementia complex and progressive multifocal leucoencephalopathy was observed, as well as in those with opportunistic infections of the central nervous system (p < 0.0001). In particular, a significant decrease in fibronectin concentration in cerebrospinal fluid was observed in patients with cerebral toxoplasmosis and cryptococcal meningitis (p < 0.0001). CONCLUSIONS--Because fibronectin can bind to several viruses, fungi, and protozoa, it is conceivable to suppose that the consumption of fibronectin in the cerebrospinal fluid of patients with neurological disorders may be related to the binding of fibronectin to HIV itself, or to viral proteins, or to organisms responsible for opportunistic infections.